2-Styrylchromones as novel inhibitors of xanthine oxidase. A structure-activity study - Fernandes, Eduarda (2002)
The purpose of this study was the evaluation of the xanthine oxidase (XO) inhibition produced by some synthetic 2-styrylchromones. Ten polyhydroxylated derivatives with several substitution patterns were synthesised, and these and a positive control, allopurinol, were tested for their effects on XO activity by measuring the formation of uric acid from xanthine. The synthesised 2-styrylchromones inhibited xanthine oxidase in a concentration-dependent and non-competitive manner. Some IC50 values found were as low as 0.55mM, which, by comparison with the IC50 found for allopurinol (5.43 mM), indicates promising new inhibitors. Those 2-styrylchromones found to be potent XO inhibitors should be further evaluated as potential agents for the treatment of pathologies related to the enzyme’s activity, as is the case of gout, ischaemia/ reperfusion damage, hypertension, hepatitis and cancer.